A COMPARISON OF SEAL PRESSURE OF I-GEL BEFORE AND AFTER INSERTION OF A GASTRIC TUBE - Saleem Nawaz; Anser Ali Butter (Journal of University Medical & Dental College, 2012)
ABSTRACT Background: I-gel is a new supraglottic device, which is comparable with classical LMA for its seal and ease of insertion. It has an additional port for insertion of gastric tube. We studied whether insertion of a gastric tube has any effect on the seal pressure of I-gel. The present study was conducted in 30 ASA I and II patients undergoing general anesthesia. The aim was to study the difference in the seal pressure of I-gel before and after insertion of gastric tube. Methods: Water lubricated I-gel was inserted in 30 patients 1 minute after induction of general anaesthesia with Propofol 2.5 mg/kg and rocuronium 0.6mg/kg I/V for muscle relaxation, according to the technique described in the manual. Seal pressure was measured using manometer before and after gastric tube insertion. Results: The subjects were 86.7% females and 13.3% males. 43.3% weighed <65kg. 83.3% belonged to ASA class I, and 16.7% belonged to ASA class II. Mean seal pressure was 23.3±8.0 millibar before gastric tube insertion through I-gel and 24.4±8.4 millibar after gastric tube. Paired sample t-test showed a P value = 0.2, which was not significant. Conclusion: Insertion of gastric tube did not influence the seal pressure of the I-gel device.